Spatial-economic framework to estimate small biomass plant remuneration in reactive power markets. (December 2021) - Laylakar, Marjhorre; Major, Lucas V.L.; Belati, Edmarcio A.; Falcão, Djalma M.; Heymann, Fabian; Melo, Joel D.
Abstract: With growing shares of renewable power generation, ancillary services such as reactive power become increasingly important to balance power systems. In this work, we provide a framework to assess the suitability of small biomass power plants, i.e., less than 5 MW, for reactive power markets. The proposed methodology consists of two-stages and considers the spatial relationship between the biomass plants' location and the regional transmission system and tests different plant remuneration scenarios. In the first step, the reactive energy potentials available from biomass plants are quantified and located through spatial analysis, considering locational factors that influence the economic value that these plants bring to the ancillary services markets. Second, a financial analysis is performed to determine how each biomass plant's electricity bill can be reduced through participation in ancillary services markets. Resulting layers of geographic information provide system operators and policymakers with the available reactive power potential and required financial compensation of biomass plant owners close to the electricity transmission system. The methodology is applied to a case study in São Paulo, Brazil, using data from sugar and alcohol plants installed near the regional transmission system's 138 kV lines to assess the implementation of a seasonal reactive power market. Highlights: A spatial-economic two-stage framework for analyzing reactive energy potential. Study of 52 biomass power plants below 5 MW in Sao Paulo State, Brazil. Seasonality, different load patterns and remuneration strategies were compared. Total reactive power potentials of biomass plants range between 53.58 Mvar and 62.93 Mvar.